2021
DOI: 10.1038/s41598-021-01312-4
|View full text |Cite
|
Sign up to set email alerts
|

The first edentulous ceratosaur from South America

Abstract: The recognition of ontogenetic edentulism in the Jurassic noasaurid Limusaurus inextricabilis shed new light on the dietary diversity within Ceratosauria, a stem lineage of non-avian theropod dinosaurs known for peculiar craniomandibular adaptations. Until now, edentulism in Ceratosauria was exclusive to adult individuals of Limusaurus. Here, an exceptionally complete skeleton of a new toothless ceratosaur, Berthasaura leopoldinae gen. et sp. nov., is described from the Cretaceous aeolian sandstones of the Bau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…This again contradicts the hypothesis that Anseriformes were ancestrally terrestrial and would explain the presence of reduced rhamphothecal lamellae in extant Anhimidae (Olson and Feduccia, 1980). Anhimidae represent the only known example of rhamphothecal lamellae being present without pedal webbing in extant birds; however, similar lamellae-like ridges have been found in Ornithomimus (Norell et al, 2001; Barrett, 2005), Gallimimus, chelonians, hadrosaurs (Barrett, 2005) and an edentulous ceratosaur (Alves de Souza et al, 2021). A partial correlation between the presence of these ridges and exclusively herbivorous diet among terrestrial chelonians has been found (Bramble, 1974; Pritchard, 1979), suggesting that more prominent ridges were present when more coarse vegetation was eaten.…”
Section: Discussionmentioning
confidence: 88%
“…This again contradicts the hypothesis that Anseriformes were ancestrally terrestrial and would explain the presence of reduced rhamphothecal lamellae in extant Anhimidae (Olson and Feduccia, 1980). Anhimidae represent the only known example of rhamphothecal lamellae being present without pedal webbing in extant birds; however, similar lamellae-like ridges have been found in Ornithomimus (Norell et al, 2001; Barrett, 2005), Gallimimus, chelonians, hadrosaurs (Barrett, 2005) and an edentulous ceratosaur (Alves de Souza et al, 2021). A partial correlation between the presence of these ridges and exclusively herbivorous diet among terrestrial chelonians has been found (Bramble, 1974; Pritchard, 1979), suggesting that more prominent ridges were present when more coarse vegetation was eaten.…”
Section: Discussionmentioning
confidence: 88%
“…This again contradicts the hypothesis that Anseriformes were ancestrally terrestrial and would explain the presence of reduced rhamphothecal lamellae in extant Anhimidae [ 22 ]. Anhimidae represent the only known example of rhamphothecal lamellae being present without pedal webbing in extant birds; however, similar lamellae-like ridges have been found in Ornithomimus [ 108 , 109 ], Gallimimus, chelonians, hadrosaurs [ 109 ] and an edentulous ceratosaur [ 110 ]. A partial correlation between the presence of these ridges and exclusively herbivorous diet among terrestrial chelonians has been found [ 111 , 112 ], suggesting that more prominent ridges were present when more coarse vegetation was eaten.…”
Section: Discussionmentioning
confidence: 99%
“…The centrum is craniocaudally shorter than transversely wide, as in many other abelisaurids ( figure 3 ; table 1 ) but contrasting strongly with the much more elongate caudal cervical centra of many non-abelisaurid ceratosaurs such as Berthasaura leopoldinae [ 32 ], Elaphrosaurus bambergi [ 33 – 35 ], Limusaurus inextricabilis [ 36 ], Masiakasaurus knopfleri [ 37 , 38 ] and Vespersaurus paranaensis [ 39 ]. The centrum lacks a ventral keel, as is also the case in Majungasaurus [ 27 ] and Viavenator exxoni [ 28 , 30 ].…”
Section: Methodsmentioning
confidence: 99%